Análisis contrastivo (español-francés) de casos de variación en las nomenclaturas anatómicas - Jiménez Gutiérrez, Isabel (Anales de Filología Francesa, 2010)
Contrastive approaches are frequently employed in translators training to teach foreign languages. Systematic comparison of two languages allows to identify students’ specific difficulties. Difficulties in translating medical texts involve syntactic, stylistic and, specially, terminological problems. Nomenclatures, as, for instance, anatomical nomenclatures, contribute to communication among the different scientific communities. But terminological variation and interference phenomena are frequent, which represent an added obstacle to translation of medical texts. In this paper we intend to analyze different types of variation observed in Spanish and French anatomical nomenclatures.